Financial Feasibility Analysis of Upland Rice Farming in Ulunambo Village, North Kulisusu Subdistrict, North Buton Regency - Faldin; Iswandi, Marsuki; Rosmawaty (International Journal of Technology and Education Research, 2026)
This research aims to (1) analyze the income of field rice farming, (2) analyze the feasibility of field rice farming, (3) the minimum land area equivalent to District Minimum Wage (UMK). This research was carried out in Ulunambo Village, North Kulisusu District, North Buton Regency. The respondents in this research were 10 farmers which was carried out in June 2024. The method used in this research was quantitative analysis. The results of the research show that: (1) the average income of respondents is IDR 1,455,933/Ha/Six Months, divided by post-harvest for 6 months, the total income is IDR 242,656/Ha/Month, while income is based on the Regency Minimum Wage (UMK) North Buton gets an average income of IDR 2,758,984 per month (2) the feasibility of the R/C is 2.4, so R/C ≥ 1 (3) the minimum land area that respondents must obtain is 11.4 Ha. So it can be concluded that field rice farming in Ulunambo Village, North Kulisusu District, North Buton Regency is feasible and profitable based on the R/C calculation, but if seen in terms of monthly income, it is not feasible when compared with the North Buton Regency Minimum Wage (UMK) income